Investigating the Emergence of Candida auris in a Resource Limited setting in West Africa. (March 2022) - Agbalaya, O.; Adeleke, G.; Ettu, A.W.; Oladele, R.
Abstract : Purpose: Candida auris is an emerging pan resistant pathogen, which is of particular importance in resource limited settings such as ours, with poor availability of drugs needed to treat its infections. It was identified in 4 blood culture samples from 4 hospitals in Nigeria. Three patients were in the ICU and one was critically ill, in a Gynaecological ward. The objective of this work was to investigate the potential reservoirs of the organism in the patients' environment. Methods & Materials: Two hospitals gave consent for environmental investigation which was carried out using the environmental surveillance toolkit adapted from CDC's website. Swabs were collected from relevant environmental sources according to the toolkit's guidance. The samples were cultured on Saboraud Dextrose Agar slants at 37°C for 24 to 72 hours. Identification of yeast isolates was done using the Biomerieux Vitek® 2 Compact, data analysis was done using Microsoft Excel. Results: 141 swab samples were collected from both sites, 60(42.5%) of them yielded growth. There were 9 yeast isolates: Candida rugosa 3(33.3%) from a bedside locker, mattress and a pulse monitor; Cryptococcus laurentii 2(22.2%) from an axilla and groin composite skin swab and a sink. Candida albicans 1(11.1%) was from a bed railing, Candida lusitaniae 1(11.1%) from a bedside locker, Candida parapsilosis 1(11.1%) and Candida tropicalis 1(11.1%) was from drug carts. There were 20 mold isolates from bed railings (14;70%), drug carts (3; 15%), bedside lockers (1;5%), mattress (1;5%) and a sphygmomanometer (1;5%). There were 31(22%) bacteria isolates. No Candida auris was isolated in this study. Three patients died and one was discharged without any antifungal therapy. Conclusion: Candida auris was not isolated from the patients' environment and this is not surprising, we lacked resources to do this, like the environmental sponge sticks, circulating stomacher and the C.auris Chromagar. Interestingly, a significant number of molds were isolated from bed rails, but not surprising because we have a tropical climate and the ward windows are open. It is imperative that in view of possible outbreaks of C.auris, these resources be made available in our setting. Educating clinicians is also critical to curtail possible outbreaks.